2007
DOI: 10.1038/sj.leu.2405070
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic score for patients with lower risk myelodysplastic syndrome

Abstract: Current prognostic models for myelodysplastic syndromes (MDS) do not allow the identification of patients with lower risk disease and poor prognosis that may benefit from early therapeutic intervention. We evaluated the characteristics of 856 patients with low or intermediate-1 disease by the International Prognostic Scoring System. Mean follow-up was 19.6 months (range 1-262). Of these patients, 87 (10%) transformed to acute myelogenous leukemia, and 429 (50%) had died. By multivariate analysis, characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
229
4
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(252 citation statements)
references
References 15 publications
7
229
4
12
Order By: Relevance
“…Improvement in the IPSS scoring method has been suggested by Germing et al, who proposed adding LDH as a prognostic variable in addition to the IPSS group [38], and Garcia-Manero et al [39], who proposed refinement of criteria for classifying lower-risk groups. Here, we propose that patients with MDS stratification may be improved using additional recommended risk factors, such as those described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in the IPSS scoring method has been suggested by Germing et al, who proposed adding LDH as a prognostic variable in addition to the IPSS group [38], and Garcia-Manero et al [39], who proposed refinement of criteria for classifying lower-risk groups. Here, we propose that patients with MDS stratification may be improved using additional recommended risk factors, such as those described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…ORR and OS were also assessed according to age (aged <70 years vs !70 years), transfusion dependence at baseline (no vs yes), azacitidine dose schedule (75 mg/m 2 daily vs 100 mg as a daily fixed dose), total median azacitidine dose per cycle ( 700 mg vs >700 mg), and prior therapy (no vs yes). Patients also were analyzed according to IPSS subgroups (low risk or Int-1 risk) and according to the more recent WHO-based prognostic scoring system (WPSS) 38 and The University of Texas M. D. Anderson Cancer Center (MDACC) model, 39 which is specific to lower risk MDS. Both the WPSS and the MDACC models include parameters that are not present in the IPSS, such as transfusion requirement and WHO classification 38 or age and degree of thrombocytopenia, 39 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Malcovati et al [10], Gattermann et al [19] and Garcia-Manero et al [23] also underlined a negative influence of transfusion-related iron overload on survival in MDS patients. Park et al [16] found no correlation of ferritin concentration with survival, but only with dependency of RBC-transfusions.…”
Section: Discussionmentioning
confidence: 99%